PENGARUH KEPEMIMPINAN, KEMATANGAN PEGAWAI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN BATU BARA - Irwansyah .; Robianti Siregar; Trisna Tiktawati; Rahmawati Sukra; Jan Putra Siadari (Universitas Islam Sumatera Utara, 2020)
Problem of this study it is influence of leadership on performance. It is influence of employees maturity on performance. It is influence of work environment on performance. It is influence leadership, employees maturity and work environment on performance. The purpose of this study to determine and analyze the effect of leadership on performance. Determine and analyze the effect of employees maturity on performance. Determine and analyze the effect of work environment on performance. Determine and analyze the effect of leadership, employees maturity and work environment on performance. Sample in the study is 38 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate leadership variable has a positive and significant effect on performance. Employees maturity variable has a positive and significant effect on performance. Work environment variable has a positive and significant effect on performance. Leadership, employees maturity and work environment variable has a positive and significant effect on performance.